Effects of maternal exposure to an aromatase inhibitor on sexual behaviour and neurochemical and endocrine aspects of adult male rat - Gerardin, Daniela C. C. [UNESP]; Piffer, Renata C. [UNESP]; Garcia, Patricia C. [UNESP]; Moreira, Estefania G.; Pereira, Oduvaldo C. M. [UNESP] (CSIRO Publishing, 2008)
The present study examined the effects of letrozole exposure during brain sexual differentiation on endocrine, behavioural and neurochemical parameters in male rat descendants. Pregnant female rats received 1 mg kg(-1) day(-1) letrozole or vehicle by oral gavage on gestational Days 21 and 22. Exposure to letrozole reduced anogenital distance in males on postnatal Day (PND) 22. At adulthood (PND 75), plasma testosterone levels and hypothalamic dopaminergic activity were increased, but sexual competence was impaired, because fewer successful sexual behaviours (mount, intromission and principally ejaculation) were observed. The impairment of reproductive function by prenatal exposure to an aromatase inhibitor reinforces the importance of adequate oestrogenic activity during perinatal sexual differentiation for complete masculinisation of the hypothalamus.
Keywords: hypothalamus; neurochemistry; sexual differentiation; striatum